Electrospun BiOCl/Bi2Ti2O7 Nanorod Heterostructures with Enhanced Solar Light Efficiency in the Photocatalytic Degradation of Tetracycline Hydrochloride. Issue 11 (24th April 2018) - Xu, Yuxian; Lin, Daifeng; Liu, Xinping; Luo, Yongjin; Xue, Hun; Huang, Baoquan; Chen, Qinghua; Qian, Qingrong
Abstract: Bismuth titanates (BTs) can be fabricated by electrospinning combined with calcination at different temperatures. BiOCl/Bi2 Ti2 O7 nanorod heterostructures were obtained at 500 °C. They possess excellent photocatalytic efficiency and stability for tetracycline hydrochloride (TC‐HCl) degradation under simulated solar light. The excellent catalytic activity is predominantly attributed to the heterostructure between BiOCl and Bi2 Ti2 O7, which accelerates the separation of photogenerated carriers while the narrow band gap of Bi2 Ti2 O7 enhances solar energy utilization. On the basis of energy band engineering, scavenger tests, and LC‐HRMS analysis, a possible degradation pathway of TC‐HCl and photocatalytic mechanism were proposed. Our work can predict a facile route for achieving high photocatalytic performance of Bi2 Ti2 O7 ‐based materials in the application of TC‐HCl degradation. Abstract : Removing antibiotics from wastewater : Electrospinning combined with calcination at 500 °C produces BiOCl/Bi2 Ti2 O7 nanorod heterostructures. The material possesses excellent photocatalytic efficiency and stability for tetracycline hydrochloride antibiotic degradation under simulated solar light owing to the heterostructure between BiOCl and Bi2 Ti2 O7, which accelerates the separation of photogenerated carriers while the narrow band gap of Bi2 Ti2 O7 enhances solar energy utilization.